(untitled) (Global Psychiatry Archives, 2026)
Palliative care remains underdeveloped in Pakistan, and little is known about how patients themselves experience life-limiting illness within low-resource charitable hospitals. This study explored the lived experience of a man receiving palliative care for advanced liver malignancy in a charitable hospital in Lahore, Pakistan. Using a descriptive phenomenological design informed by Husserl and guided by Bevan’s method of phenomenological interviewing, one in-depth, semi-structured interview was conducted in the participant’s home. Data were analysed through phenomenological reduction, transformation of meaning units, imaginative variation, and synthesis into a structural description. The findings reveal a complex, deeply embodied and emotionally layered experience in which illness, poverty, spirituality and family responsibility are inseparably intertwined. The participant described illness as an all-encompassing disruption marked by severe physical suffering, fluctuating crises, delayed diagnosis and persistent uncertainty about death. Material hardship permeated his narrative, with poverty shaping access to care, travel, nutrition, and the ability to provide for his children. Spiritual reflection and surrender to divine will offered meaning, while humour and moral integrity helped preserve dignity. He expressed profound gratitude for the charitable hospital, describing the staff’s compassion, clarity of communication and respectful treatment as life-affirming and protective. Near-death episodes heightened awareness of mortality, yet acceptance emerged not as a linear psychological stage but as a culturally grounded, spiritually framed process aligned with Islamic and Sufi-inflected understandings of life’s cycles. This study highlights the significance of culturally attuned, holistic palliative care that addresses physical symptoms alongside socioeconomic, familial and spiritual concerns. It underscores the centrality of compassion, trust and clear communication in restoring dignity for patients facing serious illness in resource-constrained settings. Phenomenological insights from this single case emphasise the need for expanding culturally informed palliative care research and practice in Pakistan.